Ether functionalisation, ion conformation and the optimisation of macroscopic properties in ionic liquids. Issue 40 (13th October 2020) - Philippi, Frederik; Rauber, Daniel; Kuttich, Björn; Kraus, Tobias; Kay, Christopher W. M.; Hempelmann, Rolf; Hunt, Patricia A.; Welton, Tom
Abstract : The dynamics and liquid structures of ionic liquids are significantly influenced by the preferred geometries and the flexibilities of both cations and anions. Abstract : Ionic liquids are an attractive material class due to their wide liquid range, intrinsic ionic conductivity, and high chemical as well as electrochemical stability. However, the widespread use of ionic liquids is hindered by significantly higher viscosities compared to conventional molecular solvents. In this work, we show how the transport properties of ionic liquids can be altered significantly, even for isostructural ions that have the same backbone. To this end, structure–property relationships have been determined for a set of 16 systematically varied representative ionic liquids. Variations in molecular structure include ammonium vs. phosphonium, ether vs. alkyl side chains, and rigid vs. flexible anions. Ab initio calculations are used to relate molecular structures to the thermal, structural and transport properties of the ionic liquids. We find that the differences in properties of ether and alkyl functionalised ionic liquids are primarily dependent on minimum energy geometries, with the conformational flexibility of ether side chains appearing to be of secondary importance. We also show unprecedented correlations between anion conformational flexibility and transport properties. Critically, increasing fluidity upon consecutive introduction of ether side chains and phosphonium centres into the cation is found to be dependent on whether the anion is flexible or rigid. We demonstrate that targeted design of functional groups based on structure–property relationships can yield ionic liquids of exceptionally high fluidity.